miR-200a-3p Regulates PRKACB and Participates in Aluminium-Induced Tau Phosphorylation in PC12 Cells - Huan Li; Qun Liu; Qinli Zhang; Xingli Xue; Jingsi Zhang; Jing Zhang; Li Lin; Qiao Niu (Neurotoxicity Research, 2022)
Aluminium (Al) is an environmental neurotoxin that humans are widely exposed to, but the molecular mechanism of its toxic effects is not fully understood. Many studies have shown that exposure to Al can cause abnormal phosphorylation of the tau protein that is believed as one of pathological features of Alzheimer’s disease. Increasing evidence indicates that microRNAs (miRNAs) may be involved in the pathological processes of neurodegenerative diseases and are potential regulatory factors for related target genes. Phosphorylation at Ser-133 of cAMP response element-binding protein (CREB) is one of the major pathways of CREB activation, and phosphorylation at this site is controlled by protein kinase A (PKA). The catalytic subunit of PKA, cAMP-dependent protein kinase catalytic subunit beta (PRKACB), phosphorylates CREB. The target gene prediction software TargetScan showed that PRKACB was one of the target mRNAs of miR-200a-3p. The purpose of this study was to investigate whether miR-200a-3p regulates the PKA/CREB pathway by targeting PRKACB and leads to abnormal phosphorylation of the tau protein in nerve cells. The results showed that Al exposure increased the expression level of miR-200a-3p, and miR-200a-3p increased the expression of targeted downregulated PRKACB, and then decreased the PKA/CREB signalling pathway activity, leading to abnormal hyperphosphorylation of tau. Graphical Abstract